Correlation of Dysmenorrhea with training hours among ball badminton players - P.PONMATHI; SHALINI NAIR KRISHNAN; V.P.R.SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2018)
While exercise provides substantial health benefits, rigorous physical activity is also associated with a unique set of risks for the female athlete. The female reproductive system is highly sensitive to physiological stress, and reproductive abnormalities, including delayed menarche, primary and secondary amenorrhea occurs in women engaged in athletic activity. Thus the aim of the study is to find out the correlation of dysmenorrhea with training hours among ball badminton players. 81 ball badminton players were recruited for the study. After the informed consent was taken from the players as well as coaches of the individual teams, all the players filled a questionnaire which included demographic data, menstrual history and their training hours. All the data collected was entered into MS excel and statistical analysis was performed using SPSS 16 software. There is no correlation (r = 8.916, p<0.05) of dysmenorrhea with training hours among ball badminton players. There exist a statistically significant correlation between training hours and dysmenorrhea among ball badminton players.